Identification of cultural properties of Arab District, Erbil, Iraq - Akram, Omar Khasro (2017)
This research aims to identify cultural properties of the Arab District, located in Erbil City, Iraq. Being one of the oldest constantly inhabited cities, Erbil City has great heritage and cultural values, including its Citadel, which is in UNESCO’s World Heritage List since 2014. This district was the first inhabited area outside the citadel and, similarly to it, has highly influenced the urban fabric growth of the city and implemented the same kind of buildings, houses, construction materials and ancient techniques as the ones present inside the Citadel. However, there is no reliable information about the district neither available documents for visitors, researchers or planners to consult. In order to address this issue this thesis aims to identify the criteria based on UNESCO requirement operational guidelines 2015 and analyse the cultural properties present in Arab District, proposing a documentation framework that should be archived for the need of future conservation works. Using Arab District as a case study, the research adopts a qualitative method in order to collect and analyse relevant information, including municipality documents, observations, photographs and interviews with authorities and specialists to confirm the authenticity of the data collected. In order to better understand the cultural properties of the area, factors like historical background, urban fabric, buildings and house typologies, are deeply analysed. As main findings it is important to highlight the two types of house typologies, composed by one or two floors, the three different types of courtyards, where they are classified according to their rooms’ location and the simplicity of the house facades built with bricks covered with shinny straw. It is also important to mention the uniqueness of the types of facades elements, where it is possible to find unique decorative elements, original voids, carpentry of doors and windows, exterior finishing and even internal facades. Focusing on urban, the main findings focus on the urban form of Arab District, which was kept until nowadays and represents almost a triangular shape. Narrow streets with high spatial enclosure, promotes a higher social interaction. The results must be stored in a database and turned available to the public, organized in accordance to their nature and type, in an easy way to retrieve, understand and consult.